Indonesian Tourists’ Preferences Influence of Conscious and Unconscious Motives - Ismayanti, Ismayanti; Djamhur, Ina; Levyda, Levyda (Journal the Winners: Economics, Business, Management, and Information System Journal, 2011)
Motivation is the foremost variable to explain the travel preferences. It is identified that there are two motives of travelling: inner intention as the unconscious motives and outer magnet as the conscious motives. Inner intentions derive from tourists’ mindset and push the actor to perform. Outer magnet is created by destination (tourism supplier, operators, hotelier etc.) to pull the customers. From 331 respondents in Jakarta (capital city) and Bandung as tourist generating regions in Indonesia showed that there are partial element of inner intention that encourage Indonesian to travel: religiousness and leisure time, and there are collective element of outer magnet that fascinate Indonesian tourist: cultural attraction and activities, outrange between domicile region and destination, and sophisticated amenities.